TRADISI MARTAROMBO DALAM INTERAKSI SOSIAL MASYARAKAT SUKU MANDAILING DI KOTA PEKANBARU - Andri Andika; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was carried out in pekanbaru city covering several sub-districts namely Tampan District, Sukajadi District, Marpoyan Damai District and Payung Sekaki Sub-District which is the residential area of research informants. The purpose of this study was to find out the meaning of martarombo in the social interaction of Mandailing tribe and to know the social sanctions given against Mandailing people who violated or did not run martarombo in Pekanbaru City. The theory used is the theory of symbolic interactionism and social norms. The technique of determining research informants is carried out by purposive sampling, namely selecting and assigning informants in accordance with the objectives of the research, the number of informants in this study as many as five (5) people, the authors use descriptive qualitative research methods with data collection methods are interviews and documentation. Based on the findings of the study, martarombo is a way of interacting that is hereditary carried out by the nomads of the Mandailing tribe in Pekanbaru city to find out the genealogy of clans, paruturan, and determination of kinship between mandailing people based on dalihan na tolu. Martarombo has elements of values and social norms that contain measures and rules/guidelines in behaving and behaving that are considered good and appropriate, appropriate and correct in interacting so that the life of the Mandailing community runs in an orderly, orderly and harmonious manner in daily associations and customary events based on dalihan na tolu. As for the form of sanctions given against the Mandailing people who violate the tradition of martarombo in the form of reprimands/warnings and scorn. Keywords: Martarombo, Social Interaction, Meaning, Norms and Social Values